Sampling technique and detection rates of oropharyngeal and anorectal gonorrhoea using nucleic acid amplification tests in men who have sex with men. (13th November 2017) - Yang, Tim Z T; Chen, Marcus Y; Read, Tim R H; Needleman, Robert; Bradshaw, Catriona S; Fortune, Ria; Fairley, Christopher K; Chow, Eric P F
Abstract : Objectives: The objective of this study was to examine the associations between clinicians' self-reported sampling technique and the detection rate of gonorrhoea at the oropharynx and anorectum using a highly sensitive nucleic acid amplification test (NAAT). Methods: We analysed oropharyngeal and anorectal gonorrhoea swab results among men who have sex with men attending the Melbourne Sexual Health Centre (MSHC) between March 2015 and December 2016. Swabs were tested by NAAT using the Aptima Combo 2 transcription-mediated amplification assay due to its high sensitivity. Clinicians at MSHC were invited to complete a questionnaire on sampling techniques in November 2016. Univariable generalised estimating equations (GEE) logistic regressions were performed to determine the association between gonorrhoea detection rates and clinicians' sampling technique. Patients' epidemiological risk factors were included in the multivariable GEE logistic model. Results: A total of 2605 oropharyngeal gonorrhoea and 2392 anorectal gonorrhoea swab results were analysed. There was no significant difference in the detection rates of gonorrhoea between the 23 clinicians at the oropharynx (range 3.6%–16.9%, median 8.2%, P=0.302) or and anorectum (range 2.4%–17.3%, median 10.5%, P=0.177). Variations in clinicians' self-reported sampling technique were not associated with oropharyngeal or anorectal gonorrhoea detection rates after adjusting for patients' epidemiological risk factors. Conclusions: This study shows that differences in clinicians' self-reported sampling technique did not result in measurable differences in the detection rate for oropharyngeal or anorectal gonorrhoea when using NAAT.